Enhancing the Cyclability of VS4 Positive Electrode in Carbonate‐Based Electrolyte using Fluoroethylene Carbonate Additive. Issue 6 (9th March 2022) - Yoshii, Kazuki; Kohno, Kazushige; Maeyoshi, Yuta; Taguchi, Noboru; Yano, Akira; Takeuchi, Tomonari; Sakaebe, Hikari
Abstract: Vanadium polysulfide (VS4 ) is a promising material of construction for positive electrodes of next‐generation batteries due to its high theoretical capacity and electrical conductivity compared to those of elemental sulfur. In this study, we investigated the charge and discharge behavior of a low‐crystalline VS4 positive electrode using different electrolytes and under differing charge and discharge conditions. The electrolyte composed purely of cyclic carbonate exhibited higher cycle performance than the one containing linear carbonate. Furthermore, the addition of fluoroethylene carbonate (FEC) to the electrolyte was very effective to improve the cycle performance. The effects of FEC on the VS4 positive electrode were investigated using electrochemical techniques, X‐ray photoelectron spectroscopy, and electron microscopy, the results whereof indicated that LiF‐containing components were formed on the VS4 surface, and probably contributed to the improvement of the charge and discharge behavior of the VS4 positive electrode. Abstract : Electrolyte additive matters : The charge and discharge behavior of a low‐crystalline VS4 positive electrode was investigated using different electrolytes and under differing charge and discharge conditions. Cycle stability was improved by adding FEC into the electrolyte. The formation of F‐containing compounds on the active materials was suggested by XPS and STEM‐EELS.